Optimization of Microwave-Assisted Extraction of Phenolics From Purple Star Apple (Chrysophyllum cainito L.) Peel by Response Surface Methodology - Vu, Linh Tran Khanh; Le, Ngoc Lieu (Journal of Technical Education Science, 2026)
Microwave-assisted extraction (MAE) was applied to extract phenolic compounds from purple star apple (Chrysophyllum cainito L.) peel. Process variables were optimized using response surface methodology based on a Box–Behnken design, considering ethanol concentration, solvent-to-solid ratio, and microwave duration as key factors. Total phenolic content (TPC) and antioxidant capacities, determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays, served as response variables. The fitted models showed high significance (R² > 0.99, p < 0.05) and predicted the optimal conditions of 81% ethanol, 26:1 mL/g solvent-to-solid, and 64 s microwave time. Experimental outcomes under these conditions – 168.2 mg gallic acid equivalents (GAE)/g dry weight (dw) for TPC, 243.5 mg ascorbic acid equivalents (AAE)/g dw for DPPH, and 158.4 mg AAE/g dw for FRAP – were in close agreement with predictions. Compared with maceration (12 h and 24 h, 81% ethanol, 26:1 mL/g solvent-to-solid ratio), MAE achieved superior or comparable phenolic yield and antioxidant activity within a much shorter extraction time, confirming its effectiveness as a rapid and sustainable extraction approach for fruit by-products.